The Effect of Emotional Intelligence and Motivation on Learning Outcomes of Islamic Religious Education at Vocational High School Mitra Bhakti - Hayati, Nur; Jaenullah, Jaenullah; Jannah, Siti Roudlotul; Usada, Bagus (CV. Creative Tugu Pena, 2022)
One indicator of success in achieving educational goals can be seen from student learning outcomes during learning and learning activities. Student achievement in learning outcomes cannot be separated from various factors that affect learning itself. Factors that affect student learning outcomes include internal factors and external factors. Internal factors are one of the factors that come from within students because in the teaching and learning process students are the main target. This research is quantitative research with the type of ex-post facto which aims to determine whether there is an influence of emotional intelligence and learning motivation on the learning outcomes of Islamic religious education. Data were obtained by observation, questionnaire (questionnaire) and documentation. The findings are that: First; From the results of hypothesis testing, it is known that the regression coefficient of emotional intelligence and learning outcomes is obtained by the regression equation Y=?34,174???+ 0,520????X. Second, learning motivation has a significant effect on PAI learning outcomes. From the results of hypothesis testing, the equation Y= 38.067??+ 0.493X . Third, emotional intelligence and learning motivation together have a significant effect on the learning outcomes of Islamic Religious at Vocational High School Mitra Bhakti, Bandar Sribhawono. From the calculation of multiple linear regression (multiple) obtained equation =?=25,306??+?0,406X1+??0,250??X2. The constant 25,306? describes the magnitude of learning outcomes if it is influenced by emotional intelligence and learning motivation. The regression coefficient0.406 ? describes the magnitude of the increase in learning outcomes, if accompanied by emotional intelligence variables, while the regression coefficient b2of 0.250? describes the magnitude of the increase in learning outcomes if accompanied by learning motivation. Keywords: Emotional Intelligence, Learning Outcome, Learning Motivation